2014
DOI: 10.1120/jacmp.v15i5.4921
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of interfractional variation of the breast surface following conventional patient positioning for whole‐breast radiotherapy

Abstract: The purpose of this study was to quantify the variability of the breast surface position when aligning whole-breast patients to bony landmarks based on MV portal films or skin marks alone. Surface imaging was used to assess the breast surface position of 11 whole-breast radiotherapy patients, but was not used for patient positioning. On filmed fractions, AlignRT v5.0 was used to capture the patient's surface after initial positioning based on skin marks (28 “preshifts” surfaces), and after treatment couch shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 13 publications
(17 reference statements)
7
73
0
5
Order By: Relevance
“…The patient setup used in this study was generally similar to other CBCT-based studies, most using immobilisation device to support patients' arms for stability. The results for CBCT-S were also similar to those reported by Padilla et al 31 where optical surface verification tools were used to measure setup errors with approximately 1 mm difference in systematic and random errors between the two studies. All three registration methods in this study utilised different regions of interest.…”
Section: Discussionsupporting
confidence: 85%
“…The patient setup used in this study was generally similar to other CBCT-based studies, most using immobilisation device to support patients' arms for stability. The results for CBCT-S were also similar to those reported by Padilla et al 31 where optical surface verification tools were used to measure setup errors with approximately 1 mm difference in systematic and random errors between the two studies. All three registration methods in this study utilised different regions of interest.…”
Section: Discussionsupporting
confidence: 85%
“…In patients with pendulous breast tissue, alignment based solely on bony anatomy can lead to discrepancies in the breast surface position. 29 No pendulous breasts were observed in this study, and the differences between bony alignment and soft tissue alignment were less than 5 mm for all patients. Although treatment setup was limited to weekly portal imaging verification, minimal setup variations between image guidance sessions were observed.…”
Section: Discussionmentioning
confidence: 74%
“…AlignRT to reduce setup errors as but an average of 9 mm shifts remain when compared to portal imaging [20]. Another similar study of this technique showed mean displacements were 4.1 ± 2.6 mm, 2.7 ± 1.4 mm, and 2.6 ± 1. .…”
Section: Discussionmentioning
confidence: 90%